RNAi Screening with Self-Delivering, Synthetic siRNAs for Identification of Genes That Regulate Primary Human T Cell Migration. (September 2015) - Freeley, Michael; Derrick, Emily; Dempsey, Eugene; Hoff, Antje; Davies, Anthony; Leake, Devin; Vermeulen, Annaleen; Kelleher, Dermot; Long, Aideen
Screening of RNA interference (RNAi) libraries in primary T cells is labor-intensive and technically challenging because these cells are hard to transfect. Chemically modified, self-delivering small interfering RNAs (siRNAs) offer a solution to this problem, because they enter hard-to-transfect cell types without needing a delivery reagent and are available in library format for RNAi screening. In this study, we have screened a library of chemically modified, self-delivering siRNAs targeting the expression of 72 distinct genes in conjunction with an image-based high-content-analysis platform as a proof-of-principle strategy to identify genes involved in lymphocyte function-associated antigen-1 (LFA-1)-mediated migration in primary human T cells. Our library-screening strategy identified the small GTPase RhoA as being crucial for T cell polarization and migration in response to LFA-1 stimulation and other migratory ligands. We also demonstrate that multiple downstream assays can be performed within an individual RNAi screen and have used the remainder of the cells for additional assays, including cell viability and adhesion to ICAM-1 (the physiological ligand for LFA-1) in the absence or presence of the chemokine SDF-1α. This study therefore demonstrates the ease and benefits of conducting siRNA library screens in primary human T cells using self-delivering, chemically modified siRNAs, and it emphasizes the feasibility and potential of this approach for elucidating the signaling pathways that regulate T cell function.